Teletrabajo, estrés y su impacto en el desempeño y satisfacción laboral de los trabajadores de empresas multinacionales - Garay Arauzo, Paola Natalia (2023)
Telecommuting has been developing and being implemented worldwide for several years; It is since the start of the Covid-19 pandemic, in March 2020, that this work method/concept has become more relevant across all sectors due to the restrictions and health policies imposed by governments in this context. The present research aims to determine the influence of technological difficulty, job characteristics, mediated by technostress and stress, on the performance and job satisfaction of workers who telework in a multinational company. To do this, a sample of 132 teleworkers residing in Peru and 52 teleworkers in Chile was taken using the questionnaire instrument. The methodology used is PLS-SEM (Partial Least Square Structural Equation Modeling), which responds to a multivariate analysis technique. This methodology allows to confirm the proposed conceptual model and analyzing the correlation between the study variables. According to the conceptual model presented, a direct relationship is concluded between the independent variables: technological difficulty and characteristics of the work; and the dependent variables: techno-stressors and stress, respectively. While the stress variable is inversely related to the job satisfaction and job performance variables. This research contributes to the academic community in the labor and social aspect in a context of constant change, highlights the importance of the worker's well-being and the effect that this can have on the worker's satisfaction and job performance.